(3TQM cJGH Gdjejfis - (3eMehO Hf YeQ GdfjSGHhQjs
(3ChdgG (B:s
(3GdMeO ddg GdeMehO Ydi Gdjef GdaGFV Yf jejfg GdSNGA , hGdTcQ ddQMef GdeYHhO ef GdjS GdUGOQ Yf jSGQ aVdg GdgWdGA s
(3BNQgG (B:s
(3hGSJNda GdSdWGf Ydi SLSJGf GdeYQha GdMGLH Je GdOaJQ GdChd HMeO Gddg hMSf Jhajbg Ydi jOi eDdag GdfOGJi eMehO Hf YeQ GdfjSGHhQi dhGbY SfI (B713 (3g` s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs